Role of Multimodal Imaging in Patients With Suspected Infections After the Bentall Procedure - Martina Sollini (Frontiers Media S.A., 2021)
Purpose: This study aimed to assess the diagnostic performances of multimodal imaging [i.e., white blood cell single-photon emission computed tomography/CT (99mTc-HMPAO-WBC SPECT/CT) and 18-fluoride-fluorodeoxyglucose positron emission tomography/CT ([18F]FDG PET/CT)] in patients with suspected infection after the Bentall procedure, proposing new specific diagnostic criteria for the diagnosis.Methods: Between January 2009 and December 2019, we selected within a cardiovascular infections registry, 76 surgically treated patients (27 women and 49 men, median 66 years, and range 29–83 years). All the patients underwent molecular imaging for a suspected infection after the replacement of the aortic valve and ascending aorta according to the Bentall procedure. We analyzed 98 scans including 49 99mTc-WBC and 49 [18F]FDG PET/CT. A total of 22 patients with very early/early suspected infection (<3 months after surgery) were imaged with both the techniques. Positive imaging was classified according to the anatomical site of increased uptake: to the aortic valve (AV), to both the AV and AV tube graft (AVTG) or to the TG, to surrounding tissue, and/or to extracardiac sites (embolic events or other sites of concomitant infection). Standard clinical workup included in all the patients having echocardiography/CT, blood culture, and the Duke criteria. Pretest probability and positive/negative likelihood ratio were calculated. Sensitivity and specificity of 99mTc labeled hexamethylpropylene amine oxime-WBC SPECT/CT (99mTc-HMPAO-WBC SPECT/CT) and [18F]FDG PET/CT imaging were calculated by using microbiology (n = 35) or clinical follow-up (n = 41) as final diagnosis. 99mTc-HMPAO-WBC scintigraphy and [18F]FDG PET/CT findings were compared with 95% CIs by using the McNemar test to those of echocardiography/CT, blood culture, and the Duke criteria.Results: Sensitivity, specificity, and accuracy of 99mTc-HMPAO-WBC were 86, 92, and 88%, respectively, with a slightly higher sensitivity for tube graft infection (TGI) as compared to isolated AV and combined AVTG. Overall, sensitivity, specificity, and accuracy of [18F]FDG PET/CT were 97, 73, and 90%, respectively. In 22 patients with suspected very early and early postsurgical infections, the two imaging modalities were concordant in 17 cases [10 true positive (TP) and 7 true negative (TN)]. [18F]FDG PET/CT presented a higher sensitivity than 99mTc-HMPAO-WBC scan. 99mTc-HMPAO-WBC scan correctly classified as negative three false-positive (FP) PET/CT findings.Conclusion: Our findings supported the use of 99mTc-HMPAO-WBC SPECT/CT and [18F]FDG PET/CT in patients with suspicion infection after the Bentall procedure early in the course of the disease onset to confirm the diagnosis and provide a comprehensive assessment of disease burden through the proposed criteria.